Factors Influencing Purchase Intention of Men's Skincare Products in Indonesia - Imas Pradita Pradita; Fikri Farhan (Keizai, 2026)
This study aims to examine the factors influencing the intention to purchase skincare products among men in Indonesia. The study employs a quantitative research method. The data used in this research are primary data collected through a questionnaire. The sampling technique applied is non-probability sampling using the snowball sampling method. The sample criteria consist of men aged 17–55 years who have never purchased skincare products. A total of 307 respondents participated in this study. The data analysis technique used is Partial Least Squares Structural Equation Modelling (PLS-SEM) with the SmartPLS application version 4.1.1.6.The results of this study show that social media use has a positive effect on the intention to purchase skincare products. Self-image concern does not have a significant effect on the intention to purchase skincare products. Social media use positively influences self-image concern. However, self-image concern does not mediate the relationship between social media use and the intention to purchase skincare products. Health concern has a positive effect on the intention to purchase skincare products. Meanwhile, skin health concern does not have a significant effect on the intention to purchase skincare products. Social media use also has a positive effect on health concern. Health concern partially mediates the relationship between social media use and the intention to purchase skincare products. Masculinity does not have a significant effect on the intention to purchase skincare products. Skincare perception has a positive effect on the intention to purchase skincare products.